LITERATURE STUDY OF ANTIBIOTIC RESISTANCE ESCHERICHIA COLI IN RIVER BASINS IN INDONESIA - Roshelmi Talita Subu Taopan; Novalino Harold Geofrey Kallau; Nemay Anggadewi Ndaong; Fhady Risckhy Loe (Buletin Veteriner Udayana, 2026)
Escherichia coli (E. coli) is an important indicator of faecal contamination in aquatic environments and has been increasingly reported as a reservoir of antibiotic resistance in river ecosystems. This study aimed to review the prevalence and antibiotic resistance patterns of E. coli isolated from river basins in Indonesia through a literature review approach. Scientific articles published in national journals between 2014 and 2024 were collected and analysed descriptively. The results showed that the prevalence of E. coli in river water ranged from 68.51% to 100%. High resistance levels were reported against β-lactam antibiotics, particularly ampicillin and amoxicillin (45-82%), followed by tetracycline (37-71%), streptomycin (73.3%), and tobramycin (57%). In addition, multidrug-resistant (MDR) isolates were identified in several studies, with multidrug-resistant (MDR) prevalence reaching approximately 24% in the Citarum River. These findings indicate that river basins in Indonesia may act as reservoirs for antibiotic-resistant E. coli, highlighting the importance of routine environmental monitoring and proper wastewater management to reduce the spread of antimicrobial resistance.